2005
DOI: 10.1016/j.otohns.2005.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhage Risk After Quinsy Tonsillectomy

Abstract: The goal of the study was to evaluate the incidence and possible predictive factors of post-tonsillectomy hemorrhage (PTH) in patients with peritonsillar abscess, treated by acute abscess tonsillectomy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 23 publications
(53 reference statements)
4
24
0
Order By: Relevance
“…This study investigated the different risk factors for PTH after TE and abscess-TE. In accordance with the literature, no significant relationship was found between PTH and smoking [34], regular alcohol consumption, diabetes, hypertension [35], antihypertensive therapy, postoperative pain medication with NSAIDs (COX1 inhibitor) [8,36] or opioids [8], application of glucocorticoids [8,37], therapy with antibiotics [10,38], duration of hospital stay [24,39] and surgeon experience [15]. The only significant risk factor for PTH was being male, which is in line with other research groups [6][7][8][9][10][11][12][13], although others did not find a significant correlation [14][15][16][17][18].…”
Section: Discussionsupporting
confidence: 90%
“…This study investigated the different risk factors for PTH after TE and abscess-TE. In accordance with the literature, no significant relationship was found between PTH and smoking [34], regular alcohol consumption, diabetes, hypertension [35], antihypertensive therapy, postoperative pain medication with NSAIDs (COX1 inhibitor) [8,36] or opioids [8], application of glucocorticoids [8,37], therapy with antibiotics [10,38], duration of hospital stay [24,39] and surgeon experience [15]. The only significant risk factor for PTH was being male, which is in line with other research groups [6][7][8][9][10][11][12][13], although others did not find a significant correlation [14][15][16][17][18].…”
Section: Discussionsupporting
confidence: 90%
“…14,16,17,19 Only Giger et al reported a higher haemorrhagic complication rate after immediate tonsillectomy, compared with elective tonsillectomy; however, this high incidence was mainly due to patients with prior aspirin intake (because of pain) or bleeding contralateral to the abscess. 20 These authors suggested that unilateral immediate tonsillectomy should be performed to reduce the risk of contralateral morbidity.…”
Section: Published Datamentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13] Immediate tonsillectomy remains controversial, although several publications have reported the efficacy and safety of this technique as first-line treatment for peritonsillar abscess. [14][15][16][17][18][19][20][21] Immediate tonsillectomy has become a routine procedure for the management of peritonsillar abscess in our department, since its introduction in early 2007. 2 We have decided to extend the indication for immediate tonsillectomy to include firstline treatment of parapharyngeal abscess, and the early results of this procedure are presented in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…5,19 In all of our patients improvement was achieved after surgery and antibiotic therapy with amoxicillin with clavulanic acid. Diagnostic imaging may include computer tomography 11,17,20 but it seems that the main indication for hot tonsillectomy is lack of expected clinical improvement in spite of proper treatment.…”
Section: -17mentioning
confidence: 71%